Planning the training process for the preparation of high-qualification gymnasts for the Olympic Games - Salyamin, Y.; Vernyaev, O.; Omelianchyk-Ziurkalova, O.; Maksimova, Y. (Journal of Physical Education and Sport, 2020)
Purposeful planning is at the heart of the entire training process, with days, weeks, months and years of training. It is very difficult to determine what and how you should do it. It is impossible to determine everything with mathematical accuracy. However, the degree of correctness of minute, daily, and especially promising scheduling issues can be greatly enhanced by the available data of sports training theory in this direction, the experience and talent of the coach and the individual ability of the athlete. Proper planning in the system of training high-skilled gymnasts plays a large role in achieving results in competitions. On the example of the Olympic champion gymnast - Oleg Vernyaev, the planning for the Games of the XXI Olympic Games and the performance of this load and the results of competitions at which this athlete acted were analyzed. The protocols of the finalists in all-round and main competitions are analyzed: international competitions, EuropeanChampionships, World Cup, World Cups, Olympic Games in the period 2015-2016. The purpose of our work was to show how rational planning in O. Vernyaev training contributed to the high results in the competitions. Conclusions - In order to achieve great results in competitions, you need to plan the load and have a training system that includes periods, cycles and stages for many years to come.